2003
DOI: 10.1103/physrevb.68.075417
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure and stability of PdZn and PtZn alloys: Density-functional slab model studies

Abstract: Geometric parameters of binary ͑1:1͒ PdZn and PtZn alloys with CuAu-L1 0 structure were calculated with a density functional method. Based on the total energies, the alloys are predicted to feature equal formation energies. Calculated surface energies of PdZn and PtZn alloys show that ͑111͒ and ͑100͒ surfaces exposing stoichiometric layers are more stable than ͑001͒ and ͑110͒ surfaces comprising alternating Pd ͑Pt͒ and Zn layers. The surface energy values of alloys lie between the surface energies of the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
162
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(198 citation statements)
references
References 40 publications
29
162
0
1
Order By: Relevance
“…Several explanations were proposed for the remarkable alteration in the catalytic properties on certain supports, such as the formation of Pd-Zn, Pd-Ga, and PdIn alloys. By XPS and UPS valence band studies, it was found that the electronic properties of the 1:1 PdZn alloy resemble those of metallic Cu [16,17], which was confirmed by DFT density of states calculations [18,19]. Using DFT, Neyman et al [18] calculated reaction barriers for methoxy dehydrogenation to CO and H 2 on Pd, PdZn, and Cu surfaces and found similar barriers for the dehydrogenation of intermediate formaldehyde to CO on Cu and PdZn, which are both notably higher than on Pd.…”
Section: Introductionmentioning
confidence: 89%
“…Several explanations were proposed for the remarkable alteration in the catalytic properties on certain supports, such as the formation of Pd-Zn, Pd-Ga, and PdIn alloys. By XPS and UPS valence band studies, it was found that the electronic properties of the 1:1 PdZn alloy resemble those of metallic Cu [16,17], which was confirmed by DFT density of states calculations [18,19]. Using DFT, Neyman et al [18] calculated reaction barriers for methoxy dehydrogenation to CO and H 2 on Pd, PdZn, and Cu surfaces and found similar barriers for the dehydrogenation of intermediate formaldehyde to CO on Cu and PdZn, which are both notably higher than on Pd.…”
Section: Introductionmentioning
confidence: 89%
“…17 The energy of a Cu impurity in a Pd host is close to the experimental value 16 and the surface energies are consistent with the measurements 16 and first-principles studies. 18 The potential correctly predicts the system to be in the wetting regime although for a bulk alloy it favors fcc instead of the observed B2 bcc phase. 19 To identify the low-energy configurations, we employ two complementary strategies, namely, basin-hopping global optimization ͑GO͒ and activation-minimization ͑AM͒ techniques.…”
mentioning
confidence: 88%
“…Reduction of Pd supported on ZnO in H 2 at T~523 K leads to the formation of particularly stable 1:1 PdZn nanoparticles crystallizing in the tetragonal AuCu-type lattice [1,2,4]. Both experimental and theoretical studies have already addressed the important issue of surface composition and segregation trends of the Pd-Zn intermetallic system (near-surface alloy on a single crystal and 1:1 PdZn nanoparticles on ZnO [5][6][7][8][9][10][11]) as a function of the Zn:Pd ratio (Zn coverage) and the temperature. For the specific 1:1 stoichiometry, DFT calculations identified a 1:1 ratio of Pd and Zn as the most stable configuration also in the surface layer, at least from the viewpoint of surface/bulk energetics that were not affected by high gas pressures or elevated temperature [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and theoretical studies have already addressed the important issue of surface composition and segregation trends of the Pd-Zn intermetallic system (near-surface alloy on a single crystal and 1:1 PdZn nanoparticles on ZnO [5][6][7][8][9][10][11]) as a function of the Zn:Pd ratio (Zn coverage) and the temperature. For the specific 1:1 stoichiometry, DFT calculations identified a 1:1 ratio of Pd and Zn as the most stable configuration also in the surface layer, at least from the viewpoint of surface/bulk energetics that were not affected by high gas pressures or elevated temperature [8,10]. Related experimental studies of the Zn/Pd(111) system using XPS reported different stages of the alloying process as a function of temperature, among them the formation of the theoretically predicted 1:1 surface composition [5,11,12].…”
Section: Introductionmentioning
confidence: 99%